Privatization in Latin America new roles for the public and private sectors (Praeger, 1994)
"Series of well-written articles on regional privatization efforts. Separate chapters on Argentina, Brazil, Chile, and Mexico. Other topics include: 1) changing roles of the State and business, 2) recent trends in direct foreign investment, and 3) changes in Latin American equity markets. Valuable contribution"--Handbook of Latin American Studies, v. 57.. - http://www.loc.gov/hlas/